1256 Quality of General Movements After Treatment with Low-Dose Dexamethasone in Preterm Infants at Risk for Bronchopulmonary Dysplasia. (October 2012) - Hitzert, MM; Laan, ME van der; Roescher, AM; Bos, AF
Abstract : Background: Postnatal dexamethasone (DXM) is widely used to treat preterm infants at risk for bronchopulmonary dysplasia. Previously, it was reported that high-dose DXM leads to deteriorated quality of general movements (GMs). We determined neurological functioning in infants after low-dose DXM treatment, assessed by the GM-quality until three months post term. Methods: We included preterm infants, admitted to our NICU between 2010−2012 and treated with DXM (starting dose 0.25 mg/kg/d). GM-quality was assessed before (day 0), during and after treatment until three months post term. We determined the change in GM-quality by comparing the GM-quality of day 0 with the GM-quality of the last video recording. Additionally, we calculated a motor optimality score (MOS), ranging from 8 (low optimality) to 18 (high optimality). Results: Sixteen infants were included [median GA 26.9 wks (25.0–29.7); BW 800 g (620–1665)]. Before treatment, 4 infants had normal GMs which remained normal after starting treatment. GM-quality improved in 8 of 12 initially abnormal infants (Mc Nemar; P =0.008), whilst MOS slightly increased: median 10.5, 12.0 and 12.5 on days 0, 1 and 7, respectively (NS). Cumulative DXM doses, treatment duration and postnatal ages at starting DXM were not associated with change in GM-quality. Infants whose GMs improved were ventilated for a shorter period than infants whose GMs remained the same quality ( P =0.065). Conclusions: GM-quality did not deteriorate after DXM treatment but rather improved in infants with initial abnormal GMs. Our findings suggest that neurological functioning until three months post term is not adversely affected after low-dose DXM.